Risk Factors for the Development of Hypokalemia in Neonatal Diarrheic Calves. (March 2015) - Trefz, F.M.; Lorch, A.; Zitzl, J.; Kutschke, A.; Knubben‐Schweizer, G.; Lorenz, I.
Abstract : Background: Neonatal diarrheic calves have a clear negative potassium balance because of intestinal losses and decreased milk intake but in the presence of acidemia, they usually show normokalemic or hyperkalemic plasma concentrations. Objectives: To assess whether marked hypokalemia occurs in response to the correction of acidemia and dehydration and to identify factors that are associated with this condition. Animals: Eighty‐three calves with a clinical diagnosis of neonatal diarrhea. Methods: Prospective cohort study. Calves were treated according to a clinical protocol using an oral electrolyte solution and commercially available packages of 8.4% sodium bicarbonate, 0.9% saline and 40% dextrose infusion solutions. Results: The proportion of hypokalemic calves after 24 hours of treatment (19.3%) was twice as great as it was on admission to the hospital. Plasma K + after 24 hours of treatment was not significantly correlated to venous blood pH values at the same time but positively correlated to venous blood pH values on admission ( r = 0.51, P < .001). Base excess on admission (Odds ratio [OR] = 0.81, 95% confidence interval [CI] = 0.70–0.94), duration of diarrhea (OR = 1.37, 95% CI = 1.05–1.80), milk intake during hospitalization (OR = 0.54, 95% CI = 0.37–0.79) and plasma sodium concentrations after 24 hours (OR = 1.12, 95% CI = 1.01–1.25) were identified to be independently associated ( P < .05) with a hypokalemic state after 24 hours of treatment. Conclusions and Clinical Importance: Findings of this study suggest that marked depletion of body potassium stores is evident in diarrheic calves that suffered from marked metabolic acidosis, have a low milk intake and a long history of diarrhea.